Biological and Mechanical Transmission Models of Dengue Fever - Laura, Laura; Supriatna, Asep K.; Khumaeroh, Mia Siti; Anggriani, Nursanti (Communication in Biomathematical Sciences, 2019)
Dengue fever disease is caused by the dengue virus and transmitted primarily by the Aedes aegypti mosquitoes. There is no vaccine available to prevent transmission of the disease until recently which makes 30% of the worlds population is at risk of the disease. The Aedes aegypti mosquitoes are known as multiplebiters during their blood meal periods. There are two possible transmissions of the dengue virus from the mosquitoes to humans. First, infectious mosquitoes may transmit the virus through the bite to a susceptible human after the virus experiencing the extrinsic incubation period (EIP) in the body of the mosquitoes. Second, the transmission happens directly through the transfer of virus carried in the saliva of a mosquito to a susceptible human at the second bite without waiting for the EIP. The later is known as a mechanical transmission, which occurs when a susceptible mosquito bites an infectious human and almost at the same time it transmits the virus to a healthy human. Only a few literature consider this kind of dengue transmission. In this paper, we develop a mathematical model for dengue transmission by modifying the standard dengue transmission model with the presence of mechanical transmission. We show that the spreading behavior of the disease can be described by the basic reproduction number (BRN), R0. The disease will die out if R0 < 1, and it remains endemic if R0 > 1. The analysis shows that the ratio of the BRN in the presence and absence of the mechanical transmission increases as the mechanical transmission rate increases. There is also a significant change in the outbreak intensity especially when the mechanical transmission rate is greater than the biological transmission rate.